Traditional health care seeking behavior in selected wards of Lalitpur metropolitan city. - Shakya,Sony (2017)
ABSTRACT: In rural areas there is high practice of traditional healing because of inadequate health services but in urban areas there is access to modern facilities for better health but still people are relying upon traditional medications. In the urban areas people still prefer health care services from the traditional healers( Dhami, Mata and Gubhaju). The general objective of the study is to examine the present traditional health care seeking behavior in ward no. 16 and 21 of Lalitpur Metropolitan City. This study was cross-sectional descriptive study. Non-probability sampling technique was used in this study. The study covered only specific wards of Lalitpur. Questionnaire were administered to every client In traditional healer. In depth interview with healers were also taken to know about the healing practice and their situation in deep. Analysis of data was done using SPSS . Majority of the respondents who take service from traditional healer were female. Most of the respondents were Hindu. most of the respondents were Newar. Majority 85.3% of the respondents said their annual income was sufficient. There was dual situation on healing practice, most of the people apply both traditional and modern healing practice for treatment. The first preference of patients for getting treatment by people in traditional healer is still higher (40%). Respondents visit Ghubaju to treat common cold, fever, stomach ache body pain, children problem, ineffective medicinal treatment people also for family problems psychological problems, female problems and other problems respectively. Majority, said the Jharphuk procedure and Tantramantra is done by Ghubaju. Even in the urban places of our country people still depend on traditional healers because of their cultural calues, trust. 40% respondents first preference for getting treatment was from traditional healer along with that they do prefer visiting modern health care, also found that traditional healers also refer to modern health facility if could not cure them. Which is also very good point to local health services along with municipality authorities should collaborate with both traditional and modern health care services in the delivery of health care to communities and the ward level local bodies should develop an inventory to list the names of such traditional healers, so that they could be include in the orientation/training programme leading to refer to government health care service.